The Rise of Fraud Examination and Forensic Accounting in Africa: The Nigerian Experience - Herbert, Wilson E.; Tsegba, Ioraver N.; Ene, Emeka E.; Onyilo, Francis (Archives of Business Research, 2017)
This paper documents the rise of fraud examination and forensic accounting education and research in Africa, using Nigeria to mirror the development. With attendant fraud and corrupt practices in Nigeria there are muted discussions on strategic ways to build capacity in the drive to curtail these unwholesome practices. The paper concludes, inter alia, that: (i) fraud examination and forensic accounting (FEFA) education has become an indispensable subject area in the light of the challenge of fraud and corruption in Nigeria’s (and Africa’s) economy; (ii) there is currently no formal structure for FEFA education in Nigerian tertiary education system even though there is some evidence of integration of forensic accounting education at the undergraduate and postgraduate levels; and (iii) due to the skill set required, FEFA education cannot be conveniently subsumed under traditional accounting programmes. The study recommends the articulation of a clear framework for FEFA education, coordinated by tertiary education regulators and inclusion of routine forensic audits as part of the corporate governance architecture of public and private sector organizations in Nigeria.